2013
DOI: 10.1210/en.2013-1414
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Restriction During the Periconceptional Period in Normal-Weight or Obese Ewes Results in Adrenocortical Hypertrophy, an Up-Regulation of the JAK/STAT and Down-Regulation of the IGF1R Signaling Pathways in the Adrenal of the Postnatal Lamb

Abstract: Maternal dietary restriction during the periconceptional period results in an increase in adrenal growth and in the cortisol stress response in the offspring. The intraadrenal mechanisms that result in the programming of these changes are not clear. Activation of the IGF and the signal transducer and activator of transcription (STAT)/suppressors of cytokine signaling (SOCS) pathways regulate adrenal growth. We have used an embryo transfer model in sheep to investigate the impact of exposure to either dietary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
1
8
1
1
Order By: Relevance
“…These results are in agreement with Matias et al (2003), showing decreased levels of AEA in weaning offspring from dams previously exposed to a maternal caloric restriction during pregnancy and/or lactation. However, in our experiments we detected more robust alterations in endocannabinoid and NAE levels likely because preconceptional diet restriction may induce more exacerbating effects in the offspring, as reported in both cohort studies (Roseboom et al, 2006) and animal models of undernutrition (Edwards and McMillen, 2002; McMillen et al, 2004; Zhang et al, 2013), despite the lack of change in weight at birth. Consistently, we found reduced endocannabinoid levels in normoweight pups.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These results are in agreement with Matias et al (2003), showing decreased levels of AEA in weaning offspring from dams previously exposed to a maternal caloric restriction during pregnancy and/or lactation. However, in our experiments we detected more robust alterations in endocannabinoid and NAE levels likely because preconceptional diet restriction may induce more exacerbating effects in the offspring, as reported in both cohort studies (Roseboom et al, 2006) and animal models of undernutrition (Edwards and McMillen, 2002; McMillen et al, 2004; Zhang et al, 2013), despite the lack of change in weight at birth. Consistently, we found reduced endocannabinoid levels in normoweight pups.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, studies adopting animal models of suboptimal in vitro fertilization/culture have demonstrated robust metabolic alterations resulting in obesity and hepatic steatosis in the offspring (Fernández-Gonzalez et al, 2004; Serrano et al, 2014). Additionally, evidence from animal models have shown that either caloric restriction or weight loss during the periconceptional/gestational period could lead to epigenetic alterations (Raychaudhuri et al, 2008), developmental impairment of the hypothalamus (Sebert et al, 2011), altered leptin signaling (Bouret et al, 2004), alterations in blood pressure, adrenocortical growth or hypothalamus-pituitary adrenal axis in the offspring (Edwards and McMillen, 2002; McMillen et al, 2004; Zhang et al, 2013). These events may occur independently of the pre-pregnancy maternal body weight or whether an adequate maternal nutrition is provided in the later phases of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quantity of food provided was based on National Research Council recommendations, 16 and further reductions could affect nutrient status at conception and alter pregnancy outcomes. 22,23 The reduced litter sizes in dams of advanced maternal age could not be fully explained by the increased resorption rate and, therefore, may be attributed to implantation failure or peri-implantation loss; consistent with this idea, 52% of aged dams had no evidence of pregnancy at term. Previous studies have shown that advanced maternal age is associated with an impaired decidual reaction and reduced uterine prostaglandin synthesis, as well as changes in the microstructure of the uterine luminal epithelium, particularly in the microvillous architecture.…”
Section: Advanced Maternal Age and Pregnancy Outcomesmentioning
confidence: 91%
“…They include epigenetic regulation (Nijland et al, 2010; Martinez et al, 2014), leptin signaling (Yura et al, 2005; Palou et al, 2010), hypothalamic development (Sebert et al, 2009; García et al, 2010), and dopaminergic and serotonergic signaling systems (Manuel-Apolinar et al, 2014). Interestingly, recent studies have documented epigenetic modifications or affectation of adrenocortical growth in offspring after maternal dietary restriction around the time of conception (Nicholas et al, 2013; Zhang et al, 2013), pointing out the importance of the periconceptional window in the metabolic programming.…”
Section: Introductionmentioning
confidence: 99%